Sprachlich-kommunikative Anforderungen im Berufsfeld Einzelhandel - Steffan, Felix [Verfasser] (My University, 2015)
"In the ongoing discussion about communicative skills and linguistic competences as a fundamental part of vocational training there is a growing tendency towards using sophisticated needs analyses as a basis for task and content based learning. This paper describes how a vocation-bound elicitation of authentic lingustic and communicative requirements can be performed and how it can contribute to the educational instruction of linguistic and communicative skills. In order to investigate subjective and objective needs, the article proposes a composition of different methodological attempts. It is assumed that the empirically founded instructional design will positively affect motivation and learning in the context of vocational training." (author's abstract, BIBB-Doku)
Keywords: S 2.2.5 Standards in der beruflichen Bildung; L 1.6.1 Deutsch; L 2.2.2 Fach- und Technikdidaktik; S 6.4.1.1 Warenkaufleute; Sprachkompetenz; Schlüsselqualifikation; Sprachförderung; Deutschunterricht; Fachdidaktik; Berufsausbildung; Einzelhandel